(3GdJehjd GdeUQaj ddeTQhYGJs - (3QTOj UGdM YHO GdaJGM(B, (3UGdMs ((3GdbGgQI(B:s (3OGQ GdfgVI GdYQHjI,s, 2006)
(3jVe eSDhdjI GdOhdI Yf JbOje NOeGJ GdHfjI GdCSGSjI GdGbJUGOjI eaGgje heQJcRGJ CSGSjI, PGJjI GdJehjd GdeUQaj deTQhYGJ GdHfjI GdCSGSjI GdGbJUGOj, OhQ GdHfhc GdeUQjI aj Jehjd eTQhYGJ GdHfjI GdCSGSjIs
(3HjHdjhZQGajG(B: (3U(B.290s
Keywords: (3GdJehjds; (3GdJehjd(B- (3GdHfhcs; (3GdeTQhYGJ(B- (3Jehjd s